The International Diversification of Banks and the Value of Their Cross-Border M&A Advice - Rajamani, Anjana; van der Poel, Marieke; de Jong, Abe; Ongena, Steven (Management Science, 2017)
We examine the impact of the international diversification of banks on the value of their advice in 1,705 cross-border merger and acquisition (M&A) transactions. We find that bidders engaging internationally diversified advisors face lower announcement returns. An increase of one standard deviation in advisor diversification is associated with an announcement return lower by 92 basis points for a bidder acquiring a listed target. The lower bidder returns are attributable to the lower synergies of the deals being completed. Our evidence suggests that internationally diversified advisors offer lower-quality advice to their clients, since their reputational concerns are weakened by having access to multiple geographies from which they can derive fee-based income. We present further evidence that financial incentives in the form of the advisor’s involvement in deal financing and market incentives in the form of the potential to gain market share in the bidder country may mitigate some of the negative effects of the international diversification of the advisors. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2015.2396 . This paper was accepted by Wei Jiang, finance.